Periphytic algae biomass at different shading levels: an experimental approach - Santos,Helivania Sardinha dos (2021)
Abstract: Aim Light is an essential component in the process of synthesis of organic compounds by photosynthetic organisms. Assuming that a higher level of luminosity would positively influence the production of biomass, we evaluated the influence of different levels of shading on the biomass of periphytic algae, through an experimental study. Methods Glass slides were used for this as an artificial substrate for the colonization and succession of algae in Garças Lake, on the upper Paraná River floodplain, and later transferred to nine aquaria. These were divided into three treatments: three without cover (AC), three with 50% shading screens (A50) and three with 80% shading screens (A80). Abiotic variables (pH, conductivity, turbidity, temperature and dissolved oxygen) and biomass were measured every five days for 15 days. The biomass was evaluated using the chlorophyll-a method. Concentrations of total phosphorus, phosphate, total nitrogen, nitrate and ammoniacal nitrogen were evaluated every five days. Results There was no significant variation of the biomass over time, however, there is a significant difference between the treatments. The highest biomass was found in the control treatment and the lowest was found in the treatment with 80% shading. The other limnological variables evaluated did not show significant changes over time. Conclusions The abiotic variables did not influence the biomass of the phycoperiphyton community, which was influenced only by luminosity. Thus, we conclude that light is a variable with direct influence on the production of periphytic biomass. At low intensity it is a variable that can limit the production of biomass. In high intensity however, it influences by increasing its production.